Analysis Of Mathematical Literacy Of Fifth-Grade Elementary Students Based on Their Mathematical Creative Self-Efficacy Level at SD Tumbuh 1 Yogyakarta - Eliza Deviana Putri; Rina Dyah Rahmawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the analysis of Mathematical literacy of fifth-grade elementary students based on their level of Mathematical creative self-efficacy at SD Tumbuh 1 Yogyakarta. Mathematical literacy is the skill to use Mathematics to solve various problems in real life. The research is a qualitative approach. The research method used was the descriptivequalitative method. The subjects involved 6 fifth-grade students of SD Tumbuh 1 Yogyakarta. The technique analysis used the Miles and Huberman model. Data validity checks used triangulation of observation, interviews, and documentation. The research results indicate that Mathematical creative self-efficacy influences students' mathematical literacy skills. The higher the students' MCSE level was, the better their mathematical literacy skill was. The learning methods selected by teachers in implementing Mathematics learning were small and large group discussion methods, hands-on methods with games, and giving rewards or scores. The use of this learning method was adjusted to the material to be learned as well as the needs and skills of each student.